C5a2 can modulate ERK1/2 signaling in macrophages via heteromer formation with C5a1 and β‐arrestin recruitment. Issue 7 (29th April 2014) - Croker, Daniel E; Halai, Reena; Kaeslin, Geraldine; Wende, Elisabeth; Fehlhaber, Beate; Klos, Andreas; Monk, Peter N; Cooper, Matthew A
Abstract : The complement system is a major component of our innate immune system, in which the complement proteins C5a and C5a‐des Arg bind to two G‐protein‐coupled receptors: namely, the C5a receptor (C5a1) and C5a receptor like‐2 receptor (C5a2, formerly called C5L2). Recently, it has been demonstrated that C5a, but not C5a‐des Arg, upregulates heteromer formation between C5a1 and C5a2, leading to an increase in IL‐10 release from human monocyte‐derived macrophages (HMDMs). A bioluminescence resonance energy transfer (BRET) assay was used to assess the recruitment of β‐arrestins by C5a and C5a‐des Arg at the C5a1 and C5a2 receptors. C5a demonstrated elevated β‐arrestin 2 recruitment levels in comparison with C5a‐des Arg, whereas no significant difference was observed at C5a2. A constitutive complex that formed between β‐arrestin 2 and C5a2 accounted for half of the BRET signal observed. Interestingly, both C5a and C5a‐des Arg exhibited higher potency for β‐arrestin 2 recruitment via C5a2, indicating preference for C5a2 over C5a1. When C5a was tested in a functional ERK1/2 assay in HMDMs, inhibition of ERK1/2 was observed only at concentrations at or above the EC50 for heteromer formation. This suggested that increased recruitment of the β‐arrestin‐C5a2 complex at these C5a concentrations might have an inhibitory role on C5a1 signaling through ERK1/2. An improved understanding of C5a2 modulation of signaling in acute inflammation could be of benefit in the development of ligands for conditions such as sepsis.